American Social “Reminders” of Citizenship after September 11, 2001: Nativisms and the Retractability of American Identity - Fong, Jack (Qualitative Sociology Review, 2008)
My discussion considers how crisis dramatically changes social relationships and interaction patterns within a multicultural context. Specifically, I note the inherent social asymmetry of multicultural configurations, thus rendering it vulnerable for the dominant ethnic/racial group, the ethnocracy, to exact symbolically and materialistically punitive measures against minorities during periods of national crisis. I situate my discussion of dramatically changed social interactions in the post- September 11, 2001 period, when the attacks on the World Trade Center towers triggered nativism against Arab Americans, or any group phenotypically similar to the construction of “Arab.” I note how this nativism is not new but is a historical and consistent articulation of the ethnocratic stratum that retracts the American identity and notions of citizenship away from minorities during times of national crisis. The discussion concludes with how American multiculturalism is still full of unresolved ethnic and racial symbolisms that hark back to nineteenth century attempts by the White power structure to idealize, culturally and phenotypically, the constitution of an “ideal” American.